Gimnasia cerebral y la atención en los niños de inicial II del Centro de Educación Inicial José Miguel García Moreno de la ciudad de Loja, periodo 2022 – 2023 - Cabrera Cuenca, Mari Cruz (2023)
Attention is a mental process that allows focusing on relevant information and filtering out distractions. This cognitive ability directly influences a person's daily life and, therefore, is important for learning. Thus, this research aimed to identify how brain gymnastics strengthen attention in children from 4 to 5 years of age at the José Miguel García Moreno Initial Education Center. It was developed under the quasi-experimental design, with a descriptive scope and a mixed approach that allowed the collection, analysis and integration of quantitative and qualitative information; In addition, the inductive-deductive and analytical-synthetic methods were used, which were essential to carry out the investigation. In order to identify the problem, the guide for the detection and evaluation of difficulties in learning attention and memory carried out by the Ministry of Education of Bolivia was used, with nineteen children from 4 to 5 years of age, evidencing that they presented problems when executing two activities at the same time, follow instructions and complete the tasks in the determined time, observing that 21% of the children presented mild attention difficulties, after intervening with the proposal, an increase of 89% was denoted, in this attention. Regarding moderate and severe attention, initially 79% showed difficulties, then in the final evaluation, it was reduced to 11%, verifying the effectiveness of the exercises through brain gymnastics to increase concentration in the children investigated. Verifying with this research and the ones of some authors, the benefit of using brain gymnastics as a strategic tool to improve the types of selective, focused, divided and sustained attention in children, since it allows the creation of new brain connections, making their school performance favorable for their learning. Keywords: Concentration, coordination, brain exercises, children, attention span.